Inquiring into Human Enhancement - Allouche, Sylvie. author. aut Link
XVI, 278 p.
Keywords: Human enhancement has become a major concern in debates about the future of contemporary societies. This interdisciplinary book is devoted to clarifying the underlying ambiguities of these debates, and to proposing novel ways of exploring what human enhancement means and understanding what practices, goals and justifications it entails.